Nitzschia captiva sp. nov. (Bacillariophyta), the essential prey diatom of the kleptoplastic dinoflagellate Durinskia capensis, compared with N. agnita, N. kuetzingioides and other species. Issue 2 (4th March 2023) - Mann, David G.; Yamada, Norico; Bolton, John J.; Witkowski, Andrzej; Trobajo, Rosa
ABSTRACT: Durinskia capensis is a kleptoplastic dinoflagellate species from high intertidal marine rock pools, which can use a variety of diatoms for photosynthesis. However, very few of the diatoms permit indefinite survival of the dinoflagellate and rbc L sequences show that D. capensis isolated from nature contains one of two closely related Nitzschia species as its kleptoplastids. In culture, without a supply of these 'essential' Nitzschia cells to replenish the intracellular store of diatom plastids and other organelles, D. capensis eventually loses all its kleptoplastids and dies. Inside Durinskia, diatoms do not possess frustules and so cannot be compared morphologically with free-living forms. Recently, one of the essential Nitzschia species was isolated from the type locality of D. capensis and grown in culture, allowing comparison with similar Nitzschia species, particularly N. agnita and N. kuetzingioides, examined from type material. We conclude that the 'essential diatom' of D. capensis differs morphologically from these and other Nitzschia species and it is therefore described as N. captiva sp. nov. Nitzschia agnita and N. kuetzingioides, on the other hand, are conspecific and N. agnita has priority. Nitzschia captiva and N. agnita are extremely similar in valve shape, dimensions, pattern and ultrastructure, but can be separated by their girdle structure. Nitzschia agnita appears to be a freshwater species, though somewhat salt-tolerant. In contrast, N. captiva, which is known principally from records of the kleptoplastids of D. capensis rather than from frustules, is so far marine.